EFFECT OF FINANCIAL PERFORMANCE, DER, DP, COMPANY SIZE ON COMPANY VALUE ON FOOD AND BEVERAGE SECTOR - Bayu Wulandari; Yohana Meilinita Napitupulu; Naisy Margareta Lentina Cibro; Desnita Masriani Br. Sembiring; Angel Marselin Sarumaha (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
This study aims to examine the effect of Financial Performance, DER, Dividend Policy, Current Ratio, Leverage, Company Size on firm value. This research was conducted on manufacturing companies in the food and beverage sub-sector for the 2018 –u 2020 period with a population of 33 companies listed on the Indonesia Stock Exchange. The data used are the financial statements of each sample company published on the website www.idx.co.id. The research method used is descriptive analysis method and multiple linear regression analysis method. The dependent variable is firm value, while the independent variables are financial performance, DER, dividend policy, current ratio, leverage and firm size. The results of this study indicate that partially financial performance, DER, dividend policy, current ratio, leverage, firm size have an effect on firm value, but firm size has a significant effect on firm value